The Urgency of Ratifying the Appraiser Law in the Context of Providing Legal Protection for Public Appraisers in Indonesia - Javerson Simamora; Nanda Dwi Rizkia; Hardi Fardiansyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
As the scope and role of public experts continue to expand and with the increasing risks involved in carrying out public opinion work, a balance needs to be struck between legal certainty and awareness of the legal responsibility of public experts for the opinions they provide. Acquisition activities are carried out for development for the benefit of society. Public appraisers are required to be accountable for their assessments at all times. The type of research contained in this work is a type of normative legal research using statutory and case approaches. Normative legal research is research that provides a systematic explanation of the rules that apply to certain categories of laws, analyzes the relationships between rules, describes problem areas, and possibly predicts future developments. Based on the audit results, the public appraiser refers to the Regulation of the Minister of Finance